RANCANG BANGUN SISTEM INFORMASI KELAYAKAN BANTUAN SOSIAL COVID 19 BERBASIS WEB DI DESA TAPOS Design And Build A Feasibility Information System Web-Based Covid 19 Social Assistance In Desa Tapos - Mulyati, Sri; Putra, Dicky Pratama (Jurnal Teknik, 2021)
In implementing the distribution of covid 19 social assistance, the village government experienced many difficulties and protests from the community, in conducting data collection, the local RT still used the conventional system. The research objective was to find out the covid 19 social assistance system in Tapos village and the problems faced in its application. Data collection methods using observation techniques, library research and interviews. System base methodology uses the SWOT technique (Strength, Weaknesses, Opportunities and Threats). The design methodology used is the UML (Unified Modeling Language) analysis approach, and the system development method uses a waterfall which consists of requirements analysis, system design, implementation and unit testing, integration and system testing, and operation and maintenance.   Dalam pelaksanaan penyaluran bantuan sosial covid 19 pemerintah desa mengalami banyak kesulitan dan protes dari masyarakat, dalam melakukan pendataan yang dilakukan pihak RT setempat masih menggunakan sistem konvensional. Tujuan penelitian untuk mengetahui sistem bantuan sosial covid 19 di desa tapos dan masalah yang dihadapi dalam penerapannya. Metode pengumpulan data menggunakan teknik pengamatan, penelitian perpustakaan dan wawancara. Metodologi alasisis sistem menggunakan teknik SWOT (Strength, Weaknesses, Opportunities dan Threats). Metodologi perancangan yang digunakan yaitu dengan pendekatan analisa UML (Unified Modeling Languange), dan metode pengembangan sistem menggunakan waterfall yang terdiri dari analisa kebutuhan, desain sistem, implementation and unit testing, integration and system testing, dan operation and maintenance.